2016
DOI: 10.1128/jb.00166-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Neisseria gonorrhoeae Iron and Fur Regulatory Network

Abstract: The Neisseria gonorrhoeae ferric uptake regulator (Fur) protein controls expression of iron homeostasis genes in response to intracellular iron levels. In this study, using transcriptome sequencing (RNA-seq) analysis of an N. gonorrhoeae fur strain, we defined the gonococcal Fur and iron regulons and characterized Fur-controlled expression of an ArsR-like DNA binding protein.We observed that 158 genes (8% of the genome) showed differential expression in response to iron in an N. gonorrhoeae wildtype or fur str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 58 publications
1
46
0
Order By: Relevance
“…5B) but, to date, have not yet been shown to be targets of Fur. Several of these genes were also regulated via iron based on a previous analysis (17), including NGO0639, NGO2071, NGO2092, and NGO2111. In addition, several of these same genes were also regulated as a function of the absence of Fur, including NGO0639, NGO2092, and NGO2111 (17).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…5B) but, to date, have not yet been shown to be targets of Fur. Several of these genes were also regulated via iron based on a previous analysis (17), including NGO0639, NGO2071, NGO2092, and NGO2111. In addition, several of these same genes were also regulated as a function of the absence of Fur, including NGO0639, NGO2092, and NGO2111 (17).…”
Section: Resultsmentioning
confidence: 88%
“…The reasoning for this is unclear but is likely due to the fact that an environmental condition will induce changes in a greater number of genes than a genetic perturbation. As an example, studies of iron and Fur regulation in N. gonorrhoeae have found that while only 54 genes respond to a lack of the Fur protein (a genetic perturbation), 158 genes responded to changes in iron in the growth media (an environmental perturbation) (17). As transcriptomic data for N. gonorrhoeae becomes more available in the coming years, it may be beneficial to infer networks made primarily, if not completely, from transcriptomes resulting from environmental changes rather than genetic perturbations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations